Comparative Analysis of Risk-Return of Equal Weight Portfolio without rebalancing Strategy versus Passive Index Funds Investing - Parulekar, Pushkar Dilip (Chetana's Journal of Management Research, 2024)
Portfolio Diversification leads to risk reduction. Markowitz (1952) mean variance approach talks about efficient frontier. Efficient frontier is a graph of portfolios with a higher return for a given risk. This efficiency could be achieved through diversification in securities whose returns have low coefficients of correlation. The key to this process is to determine the weights of all the securities in the portfolio which could be a complex mathematical process based on historical risk and returns. An equal weight portfolio without rebalancing gives equal weight to all the securities and holds them for a long term. Passive Index funds invest in index stocks as per their weightage in index based on free float market capitalization. This study explored Nifty 50 as a base index over a period of 29 years and made various combinations equal weighted without rebalancing and index portfolios based on monthly data availability and compared their risk return performance. It also explored the performance of Nifty Equal weight index with Nifty, but the risk return for the second part was slightly in favor of Nifty index investing because of quarterly rebalancing. Quarterly rebalancing leads to money taken from gainers and investment in underperformers. This goes against the basic logic of holding on to the gainers. In all the long-term investing cases equal weight portfolio without rebalancing performed better on return/risk ratio as compared to free-float market capitalization-based index portfolio. Hence equal weight investing without rebalancing could be considered by passive retail or institutional investors.